THE PHONOLOGICAL PERSPECTIVE OF TEACHER INSTRUC TIONAL TALK IN ENGLISH CLASSROOM INTERACTION - Suharti Sirajuddin (ELT Worldwide: Journal of English Language Teaching, 2015)
The research aimed at finding and analyzing (i) the instructional talk that teachers use in the classroom interaction, (ii) teachers’ modification of their instructional talk in phonological perspective (iii) students’ perception of instructional talk used by the teachers in classroom interaction. This research applied descriptive method  with  the total number of participants of  2 English teachers and 6 students  divided based on their grade. The instrument used for this study was classroom observation, video recording and interview. The finding indicated that (i) the first participant used 15 instructional talks and the second participant used 14 instructional talks (ii) teachers modify their talk by substitution, deletion, and addition. First participant used substitution 151 times (81%), deletion 22 times (12%), and addition 13 (7%). The second participant used substitution 30 times (83%), deletion 12 times (13%) and additional 4 (4%). (iii) Students have lower perception of teacher instructional talk which indicates students get 11 (11%) for each VII grade students and the VIII grade students get variety level percentage; 12 (21%), 15(26%) and 11 (19%) for each students. It also finds three factors that influence students’ perception; teachers’ factors, limited time and environment.         Key words: Phonological perspective, instructional talk, classroom interaction